2016
DOI: 10.1007/s00203-016-1252-2
|View full text |Cite
|
Sign up to set email alerts
|

Cultivable endophytic bacteria from heavy metal(loid)-tolerant plants

Abstract: To evaluate the interactions among endophytes, plants and heavy metal/arsenic contamination, root endophytic bacteria of Prosopis laevigata (Humb and Bonpl. ex Willd) and Sphaeralcea angustifolia grown in a heavy metal(loid)-contaminated zone in San Luis Potosi, Mexico, were isolated and characterized. Greater abundance and species richness were found in Prosopis than in Sphaeralcea and in the nutrient Pb-Zn-rich hill than in the poor nutrient and As-Cu-rich mine tailing. The 25 species identified among the 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 70 publications
0
8
0
2
Order By: Relevance
“…Considering that the present experimental field contained black soil and was located within a 'golden corn belt' that accounts for approximately 40% of the national maize production in China (NBSC, 2019), the present results are important for promotion of PGPR inoculation under conservation tillage in a cold region, although application of the inoculants selected in the present study may be limited to areas with a similar soil type and climate. In addition, many previous studies have revealed that the microbial communities associated with plants (Zhang et al ., 2011; Román‐Ponce et al ., 2016) are determined by both the plant species and soil (biotic and abiotic) features. Therefore, a preferable strategy for PGPR selection and application might be to focus on efficient screening of region‐ and plant‐specific PGPR, which may have a stable effect on improvement of crop production.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the present experimental field contained black soil and was located within a 'golden corn belt' that accounts for approximately 40% of the national maize production in China (NBSC, 2019), the present results are important for promotion of PGPR inoculation under conservation tillage in a cold region, although application of the inoculants selected in the present study may be limited to areas with a similar soil type and climate. In addition, many previous studies have revealed that the microbial communities associated with plants (Zhang et al ., 2011; Román‐Ponce et al ., 2016) are determined by both the plant species and soil (biotic and abiotic) features. Therefore, a preferable strategy for PGPR selection and application might be to focus on efficient screening of region‐ and plant‐specific PGPR, which may have a stable effect on improvement of crop production.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that bacteria resistant to arsenic mostly belong to phyla Proteobacteria, firmicutes, and Actinobacteria (Sheik et al, 2012). Several genera like Bacillus, Paenibacillus, Staphylococcus, Kocuria, Sphigomonas, Arthrobacter, Brevibacterium, Pseudomonas, Microbacterium, Enterobacter, Stenotrophomonas, and Rhizobium have been reported as arsenic-resistant endophytic bacteria (Zhu et al, 2014;Román-Ponce et al, 2016Tiwari et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…En cajas de agar LB se adicionaron sales metálicas; Pb (NO 3 ) 2 , Zn (NO 3 ) 2 , Cd (NO 3 ) 2 , Cu (NO 3 ) 2 , NaAsO 2 , y NaH 2 AsO 4 , AgNO 3 , en concentraciones de ascendentes que van de 0.5 a 20 mM. La CMI se interpretó como la concentración más alta de sales en la cual no se observó crecimiento después de 7 días de exposición (Yu et al, 2014;Román-Ponce et al, 2016).…”
Section: Materiales Y Métodosunclassified
“…La minería ha generado sitios altamente contaminados con metales pesados y metaloides, ocasionando que dicha actividad sea un problema ambiental con deterioro del suelo, contaminación de aire y agua, e impacto negativo en la diversidad y riqueza de plantas, insectos y vertebrados. La diversidad y abundancia microbiana en el suelo, y en la rizosfera de las plantas que sobreviven en esos sitios, también se deteriora (Tchounwou et al, 2012;Román-Ponce et al, 2016). La persistencia de los metales en el ambiente, causa efectos adversos a los ecosistemas, y la restauración ambiental, aún es muy costosa (Mosa et al, 2016).…”
Section: Introductionunclassified